Antimicrobial resistance patterns of the Enterobacteriaceae family isolated from urinary tract infections from a Peruvian high-Andean region - Carreras, Xossé (2021)
Background: Antibiotic resistance is considered to be the next worldwide epidemic. Urinary tract infections (UTI) are the second most common cause of infection, which also has the highest resistance frequency. Nevertheless, in high Andean regions, little is known about the antibiotic resistance. Objectives : Determine the antimicrobial resistance patterns of the enterobacteriaceae family isolated from urinary tract infections of a Peruvian Andean region. Material and Methods: A retrospective cross-sectional review of 1717 records from the microbiology service of a private health institution from Puno - Peru, was done between the years 2014 and 2017. Antibiotic resistance by uropathogens was studied among different age groups. Statistical analysis included Chi2 test with a p<0.05. Poisson regression was used to calculate the prevalence ratio (PR) with a 95% confidence interval. Findings: There was a wide distribution of antibiotic resistance among all the antibiotics, mainly in Escherichia coli and Proteus spp. The elderly had the highest prevalence of antibiotic resistance. As age increased, resistance to all drugs also increased (p<0.01). Furthermore, the elderly had a risk probability of resistance of 1.22, 1.42, 1.20 and 1.32 to penicillins, cephalosporins, quinolones and other antibiotics respectively. Conclusion: The antimicrobial resistance patterns of the Peruvian Andean region were lower than national and international patterns.